Educational Impact of MP-ASI Role on Growth on Balita Stunting in Puskesmas Ujoh Bilang - Anitha Anitha; Umi Kalsum; Nilam Noorma (International Journal of Global Sustainable Research, 2023)
A change in the behavior of parents in giving MP-ASI can be done through a booster factor that is the health officer who provides health education. The aim of this research is to find out the influence of the educational role of MP-ASI on growth in stunting youngsters. This type of research is a quasi-experiment with the design of One Group Pre-Test – Post-test Design Without Control Groups. The population is the mothers who have stunts aged 6-59 months in Puskesmas Ujoh by 2022 as many as 12 people. Sampling techniques use total sampling, so samples are equal to populations. Analysis of data using paired sample t test. There is an influence of educational role MP-ASI on growth in stunting news.